Investigation of obesity levels of university students - Çınar, Vedat; Pala, Ragıp; Erdoğan, Ramazan; Öner, Salih (My University, 2016)
OBJECTIVE: The aim of this study was to determine of obesity case in students who studying at Firat university. METHODS: The research population was students studying at university in Turkey, The sample group of the survey was formed 200 (95 male, 105 female) students that studying at Firat university. At the study, nutrition habits, physical activities and diet condition scale that consists from 23 questions was applied to participants. The datas were analyzed with SPSS 22 programme. Techniques of frequencies, distribution of percents were used to analyze the data of the study. The level of significance was chosen as p <0.05 RESULTS: As a result, it is determined 48.0% of students were obes, 27.5% pre-obes,18.5% ideal and 6.0% weak. In addition it is determined 62% of students did not sport, while 38% of them did sport. CONCLUSIONS: It was observed that there were a positive relationship among nutrition habits, physical activity and inactivity.
Bildiri - Yayımlanmamış
Keywords: Obesity; Nutrition; Physical activity